STANDARD AND CONFORMITY: THE PERSPECTIVE STRATEGIES OF THE LOCAL GOVERNMENT’S ROLES IN THE INDUSTRY COMPETITIVENESS - Kharisma, Dona Budi; Imanullah, Najib; ., Pranoto (Yustisia, 2017)
The Agreement on the Technical Barriers to Trade (TBT Agreement) WTO and The ASEAN Economic Community (AEC) The Blueprint envisions the transformation of the WTO and ASEAN region through the facilitation of the free flow of goods and services. With tariffs declining to near-zero levels, non-tariff barriers are increasingly focused on coordination by member-countries. However, the quality of goods / services becomes a central issue that determines the market entry. Therefore, TBT agreement and AEC Blueprint require fulfillment of Standards and Conformity Assessment to guarantee the quality of goods or services. On the one hand, the low level of compliance of business actors in applying SNI (Indonesian National Standards) represents of the low level of Indonesian industry competitiveness in international level. Thus, specific government’s policies are required, one of which is that dealing with the strategic roles of local government to support products manufactured by national industries to break through global markets. Some strategies for strengthening local policies in national standardization include: (a) constructing local regulations governing Standards and Conformity assessment; (b) implementing mandatory SNI to leading local products; (c) Strengthening mutual cooperation between local government and related stakeholders.